Genome-wide identification, functional and evolutionary analysis of terpene synthases in pineapple. (October 2017) - Chen, Xiaoe; Yang, Wei; Zhang, Liqin; Wu, Xianmiao; Cheng, Tian; Li, Guanglin
Highlights: Identified and Classified 21 TPS genes in pineapple, Phylogenetic analysis of these TPSs show that TPSs in pineapple could be divided into 5 subfamilies. Coevolution analysis indicated that multiple amino acid residues are involved in coevolutionary processes. Combining functional divergence and molecular evolution with coevolution adds a new dimension of information to terpene synthase research. Abstract: Terpene synthases (TPSs) are vital for the biosynthesis of active terpenoids, which have important physiological, ecological and medicinal value. Although terpenoids have been reported in pineapple ( Ananas comosus ), genome-wide investigations of the TPS genes responsible for pineapple terpenoid synthesis are still lacking. By integrating pineapple genome and proteome data, twenty-one putative terpene synthase genes were found in pineapple and divided into five subfamilies. Tandem duplication is the cause of TPS gene family duplication. Furthermore, functional differentiation between each TPS subfamily may have occurred for several reasons. Sixty-two key amino acid sites were identified as being type-II functionally divergence between TPS-a and TPS-c subfamily. Finally, coevolution analysis indicated that multiple amino acid residues are involved in coevolutionary processes. In addition, the enzyme activity of two TPSs were tested. This genome-wide identification, functional and evolutionary analysis of pineapple TPS genes provide a new insight into understanding the roles of TPS family and lay the basis for further characterizing the function and evolution of TPS gene family.